Grain Phytic Acid Accumulation of Domestic and Exotic Rice Genotypes in Zinc-Deficient Soil - Nizamuddin Depar; Inayatullah Rajpar; Nabi Bux Sial; Muhammad Ibrahim Keerio (Journal of Basic & Applied Sciences, 2013)
Micronutrient malnutrition in humans living in rice growing areas is increasing rapidly due to less absorption of mineral nutrients chelated by phytic acid (anti-nutrients) present in rice grains. A field study was conducted to evaluate the grain phytic acid and zinc (Zn) accumulation of 10 field grown rice (Oryza sativa L.) genotypes on a Zn deficient soil. Both the Zn- efficient (Shua-92, IR-9, Shandar, IR-36, and IR-6) and Zn-inefficient (Sarshar,. UPL-48, Khushboo-95 and RG-120) rice genotypes were included in the study. The two Zn treatments (0 and 15 kg ha-1) were arranged in a two factor randomized complete block design with three replications. Nitrogen (N) and phosphorus (P2O5) were applied at the rate of 120 and 80 kg ha-1. The rice genotypes IR-36, UPL-79, Shandar and Shua-92 were the most Zn accumulators whereas; Sarshar, IR-9 and Khushboo-95 the least accumulator in Zn deficiency. Zinc in-efficient genotype Sarshar was the highest Zn accumulator in response to Zn application. Phytic acid content of rice genotypes was significantly influenced (p < 0.05) by the application of Zn fertilizer. Phosphorus concentration in rice grains decreased with Zn application. Zinc in-efficient genotypes accumulated more phytic acid in their food reserves than Zn-efficient genotypes. Phytic acid: zinc ratio decreased significantly more in Zn-inefficient genotypes as compared to Zn efficient genotypes, with application of Zn fertilizer. Zinc efficient genotype Shua-92 accumulated low concentration of phytic acid. The rice genotypes Shua-92, IR-9, Shandar and IR-36 low accumulators of phytic acid performed successfully and contained higher concentrations of Zn than other genotypes.